Subsea tunnel hole slag aggregate and preparation method thereof, and concrete containing subsea tunnel hole slag aggregate

By modifying the aggregate of the caverns of the seabed tunnel, the performance problems caused by high chloride ion content and many microcracks when applied in concrete are solved, and the mechanical, cracking and corrosion resistance of concrete are improved, the structural use cycle is extended and the high-value utilization of solid waste is achieved.

CN119735387APending Publication Date: 2025-04-01ANHUI UNIVERSITY OF ARCHITECTURE +1

Patent Information

Application Number
CN202411590377.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-08
Publication Date
2025-04-01

AI Technical Summary

Technical Problem

When used in concrete, the corrosion of steel bars, structural durability is affected by the high chloride ion content and the large number of microcracks, and poor mechanical and crack resistance. It is difficult for the existing technology to effectively solve these problems.

Method used

By modifying the aggregate of the cavernous tunnel, it includes reducing sulfate ion competition, blocking microcracks, wrapping controlled-release chloride ions and ion exchange curing of chloride ions, and using chemical substances such as barium hydroxide, sodium silicate, ethyl cellulose and ion exchange chitosan gel.

Benefits of technology

Effectively weaken the chloride ions and sulfate ions in the aggregate of the caverns of the sea tunnel, reduce the risk of steel bar corrosion, improve the mechanical, cracking and corrosion resistance of concrete, extend the use cycle of the engineering structure, and achieve high-value utilization of solid waste.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005125421100000101
    Figure BDA0005125421100000101
  • Figure BDA0005125421100000131
    Figure BDA0005125421100000131
  • Figure BDA0005125421100000141
    Figure BDA0005125421100000141
Patent Text Reader

Abstract

The invention discloses subsea tunnel hole slag aggregate, a preparation method thereof and concrete containing the subsea tunnel hole slag aggregate, and belongs to the technical field of building materials. The preparation method of the modified subsea tunnel hole slag aggregate comprises the following steps: S1, soaking the subsea tunnel hole slag aggregate in a barium hydroxide solution, taking out the subsea tunnel hole slag aggregate, then soaking the subsea tunnel hole slag aggregate in a sodium silicate solution, and taking out the subsea tunnel hole slag aggregate and drying the subsea tunnel hole slag aggregate; s2, soaking in an ethyl cellulose solution, taking out, drying, soaking in an ion exchange chitosan gel solution, taking out, and drying, so as to obtain a finished product; the ion exchange chitosan gel solution is prepared from nitrate radical intercalation Mg-Al-LDHs (layered double hydroxides) and chitosan hydrogel. The subsea tunnel hole slag aggregate is sequentially subjected to modification treatment of weakening sulfate ion competition, blocking micro-cracks, wrapping controlled-release chloride ions and ion exchange curing chloride ions, so that the influence of double defects of high chloride ion content and multiple cracks of the subsea tunnel hole slag aggregate on the performance of the concrete is weakened; the service life of an engineering structure is prolonged, and high-value utilization of solid waste is achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of building materials, and in particular relates to a submarine tunnel slag aggregate and a preparation method thereof, and concrete containing the same. Background Art

[0002] Undersea tunnels are one of the main forms of cross-sea passages. With the advancement of the strategy of building a strong transportation nation, my country is planning and constructing a large number of undersea tunnel projects. During the excavation of undersea tunnels, a large amount of waste slag will be generated. As the mileage of undersea tunnels increases year by year, the problem of slag disposal has become increasingly prominent. Currently, only a few tunnel slags are reasonably utilized, mainly used as road filling materials, and most of the slags are transported to waste plants for stacking or on-site burial. This treatment method not only occupies a large amount of land and destroys the local ecological balance, but also fails to achieve effective utilization of solid waste, resulting in a huge waste of resources.

[0003] At present, certain research progress has been made in the research, development and application of marine aggregates such as tunnel slag, sea sand and coral in ordinary mountainous areas and freshwater lakes in concrete. For example, Chinese Patent Application No. 202211317491.3 discloses a concrete with heated and shaped all-tunnel slag aggregates. The problems of many edges and corners and high stone powder content of fine aggregates in tunnel slag are improved by heating and shaping, and the flowability and mechanical properties of slag aggregate concrete are improved. Chinese Patent Application No. 201911145398.7 discloses a microbial sea sand concrete building material product, which uses microorganisms with mineralization and deposition functions or the function of generating polysaccharides with bonding properties to mix with sea sand, and add nutrient solution and silane coupling agent, so that the microorganisms continue to produce mineralized sediments or polysaccharides and wrap the sea sand, thereby preventing the migration of chloride ions on the surface or inside of the sea sand to the outside of the building material due to immersion in water when the sea sand is used as a building material. A polymer-based sea sand concrete disclosed in Chinese Patent Application No. 202110766228.1 uses a polymer resin to form a coating on the surface of sea sand, thereby solidifying the chloride ions in the sea sand on the concrete surface. Chinese Patent Application No. 202210866075.2 discloses a method for preparing pre-wrapped toughened coral aggregate and seawater sea sand coral aggregate concrete, which optimizes the effect of the interface transition zone between aggregate and cementitious material by adopting a strengthening method of plugging holes and building shells. However, compared with the above two types of aggregates, submarine tunnel slag integrates the shortcomings of both, and its application technical difficulties are mainly manifested in two aspects: (1) Compared with mountain and freshwater lake tunnel slag, submarine tunnel slag has been exposed to seawater immersion, penetration and chemical erosion for a long time, and has a higher content of chloride ions and sulfate ions. Its application in concrete engineering is prone to cause steel corrosion, which greatly affects the durability of the structure; (2) Compared with natural marine aggregates such as sea sand and coral, there are more micro cracks. Due to the special environment of high water pressure and chemical erosion on the seabed, coupled with the use of drilling and blasting or shield excavation, there are many microscopic cracks on the surface of submarine tunnel slag after crushing, and the mechanical and crack resistance properties of concrete are poor. However, there are few performance improvement solutions specifically for submarine tunnel slag aggregate concrete in the existing technology.

[0004] Therefore, it is of great significance to effectively weaken the adverse effects of high chloride ion content and multiple microcracks in submarine tunnel slag aggregate on concrete structure, reduce the risk of corrosion of structural steel bars, and at the same time improve the mechanical, crack resistance and corrosion resistance of concrete, so as to realize the high-value application of submarine tunnel slag solid waste in concrete. Summary of the invention

[0005] In view of the deficiencies of the above prior art, one of the objects of the present invention is to provide a method for preparing modified submarine tunnel slag aggregate, and to sequentially perform modification treatments on the submarine tunnel slag aggregate to weaken sulfate ion competition, seal microcracks, encapsulate controlled-release chloride ions, and ion exchange and solidify chloride ions, so as to weaken the influence of the dual defects of high chloride ion content and many cracks in the submarine tunnel slag aggregate on the performance of concrete, extend the service life of the engineering structure, and realize high-value utilization of solid waste.

[0006] To achieve the above purpose, the specific technical solutions of the present invention are as follows:

[0007] A method for preparing modified submarine tunnel slag aggregate comprises the following steps:

[0008] S1. Soak the submarine tunnel slag aggregate in a barium hydroxide solution, take it out and soak it in a sodium silicate solution, take it out and dry it;

[0009] S2. The tunnel slag aggregate obtained in step S1 is soaked in an ethyl cellulose solution, taken out and dried, and then soaked in an ion exchange chitosan gel solution, taken out and dried to obtain the modified submarine tunnel slag aggregate;

[0010] The ion exchange chitosan gel solution comprises nitrate intercalated Mg-Al-LDHs and chitosan hydrogel.

[0011] The modification treatment of submarine tunnel slag aggregate by the present invention is as follows: firstly, the competition of sulfate ions is weakened and micro cracks are blocked, then the slow-release layer is wrapped to control the release of chloride ions, and finally, the ion exchange layer adsorbs and solidifies the chloride ions. The specific mechanism is as follows:

[0012] Weakening the competition of sulfate ions and plugging microcracks: In addition to chloride ions, the aggregate of submarine tunnel slag also contains a large amount of sulfate ions. On the one hand, the presence of sulfate ions will promote the decomposition of Friedel's salt (with the participation of gypsum, the hydration reaction products of C3A and C4AF are chemically combined with chloride ions to form Friedel's salt, which can achieve the solidification of chloride ions) and reduce the effect of CSH solidification of chloride ions; on the other hand, the charge density of sulfate anions is relatively high, and they will compete with chloride ions during the anion replacement process. Therefore, the present invention first weakens the content of sulfate ions in submarine tunnel slag. Through immersion in barium hydroxide solution, the sulfate ions dissolved on the surface and inside of the submarine tunnel slag can combine with barium ions to form barium sulfate insoluble precipitation, greatly reducing the sulfate ion content. At the same time, the aggregate of submarine tunnel slag contains a large number of microcracks, and the barium sulfate insolubles can penetrate and fill the microcracks.

[0013] Sodium silicate has good bonding ability. Its gel formation process can effectively fix barium sulfate precipitates, improve the stability of barium sulfate precipitates and fill the micro cracks of the slag aggregate in the submarine tunnel, which has the effect of strengthening the aggregate, reducing defects and preventing water penetration. At the same time, after the concrete is formed, sodium silicate can promote the formation of CSH gel, a hydration product at the slag aggregate interface. On the one hand, it can fill the gaps at the interface of irregular slag aggregate-cement paste, increase the density of the paste, reduce drying shrinkage, and further block the slag micro cracks; on the other hand, more hydrated calcium silicate CSH gel can play a role in physical adsorption of chloride ions. The layered structure of CSH provides adsorption sites for chloride ions, which can reduce the further diffusion of chloride ions to the outside.

[0014] The slow-release layer wraps the controlled-release chloride ions: Chloride ions are polar ions that have a relatively fast diffusion rate in water. The present invention uses ethyl cellulose to wrap the slag aggregate and form a water-insoluble film on its surface. On the one hand, the hydrophobicity of ethyl cellulose can greatly reduce the diffusion rate of chloride ions in the slag aggregate into the concrete using water after the slag aggregate is added to the concrete; on the other hand, the fine pores of the ethyl cellulose membrane can achieve the slow release of chloride ions, allowing the subsequent ion exchange layer to gradually and relatively comprehensively adsorb and solidify the chloride ions. In other words, if there is no ethyl cellulose membrane, the subsequent ion exchange layer will face a high concentration of chloride ions, and the ion exchange layer will not be able to fully adsorb and solidify the chloride ions in a short time, and a large amount of chloride ions will certainly overflow into the concrete. If the ethyl cellulose membrane is completely closed (no controlled release effect), the higher alkalinity formed inside the concrete in the later stage will erode the insoluble film, and the large amount of chloride ions released will also make the ion exchange layer unable to fully adsorb and solidify.

[0015] Ion exchange layer adsorbs and solidifies chloride ions: The present invention utilizes the interlayer nitrate anions of nitrate-intercalated Mg-Al-LDHs to exchange ions with chloride ions, and adsorbs and fixes the chloride ions between the double-layer hydroxide layers, effectively reducing the free chloride ions of the submarine tunnel slag aggregate into the cement base, thereby improving the concrete's resistance to steel corrosion. However, while the nitrate-intercalated Mg-Al-LDHs solidifies the chloride ions, the nitrate ions are displaced. Nitrate ions have high diffusivity and can easily penetrate and diffuse into the interior of the concrete to react with calcium hydroxide, thereby reducing the alkalinity of the concrete, especially at the interface of the slag aggregate, and affecting the strength. Therefore, the present invention soaks the slag aggregate in a mixed solution of nitrate-intercalated Mg-Al-LDHs and chitosan hydrogel. Chitosan has cationicity and electrostatic adsorption, and its molecular structure contains a large number of amino groups. The amino groups can be protonated in the solution to form positively charged -NH3 +, electrostatic attraction can be generated between positive charges and nitrate ions, so that nitrate ions are adsorbed inside chitosan. At the same time, hydrogen bonds can be formed between the amino and hydroxyl groups of chitosan and nitrate ions, which enhances the adsorption capacity of nitrate. The concentration of nitrate ions diffused into concrete can be reduced, weakening the adverse effects of nitrate ions on concrete. In addition, powdered nitrate intercalated Mg-Al-LDHs is easy to mix unevenly when added directly to concrete. Chitosan solution can be used as a carrier, and LDHs can be evenly dispersed in the chitosan solution by pre-stirring, and evenly coated on the surface of aggregate. At the same time, when the modified submarine tunnel slag aggregate is added to the concrete, the chitosan in its outermost layer also has a good synergistic effect with the cement-based interface. On the one hand, the hydrogen bonds formed by chitosan and cement hydration products can enhance the interaction between molecules, and combined with the network structure of the chitosan solution, it can effectively improve the adhesion and crack resistance of the submarine tunnel slag aggregate and the cement-based interface; on the other hand, chitosan has excellent hygroscopicity, which can achieve internal curing effect, promote the formation of hydration products such as CSH gel at the cement-based interface of aggregate, and further improve the effect of slag aggregate in curing chloride ions and interface strength.

[0016] Preferably, the concentration of the barium hydroxide solution is 0.5-1.0 mol / L, the concentration of the sodium silicate solution is 6wt%-10wt%, and the concentration of ethyl cellulose in the ethyl cellulose solution is 12wt%-18wt%.

[0017] Preferably, the mass ratio of the nitrate intercalated Mg-Al-LDHs to the chitosan hydrogel is 1:(2.5-4).

[0018] Preferably, the chitosan hydrogel is formed by mixing chitosan with acetic acid solution, and the concentration of the chitosan is 3wt% to 6wt%.

[0019] Preferably, the ethyl cellulose solution further comprises diethyl phthalate, the mass of which is 8% to 12% of the ethyl cellulose. On the one hand, diethyl phthalate can reduce the interaction force between the molecular chains of ethyl cellulose, making the molecular chains easier to slide, thereby increasing the flexibility of the membrane and making it less likely to crack, improving the mechanical stability and extending the service life; on the other hand, diethyl phthalate can fine-tune the porosity of the ethyl cellulose membrane, thereby controlling the release rate of chloride ions.

[0020] Preferably, the immersion time of the submarine tunnel slag aggregate in the barium hydroxide solution is 8 to 10 hours, the immersion time in the sodium silicate solution is 1.5 to 2 hours, the immersion time in the ethyl cellulose solution is 40 to 60 minutes, and the immersion time in the ion exchange chitosan gel solution is 3 to 4 hours.

[0021] Another object of the present invention is to provide modified submarine tunnel slag aggregate prepared by the preparation method.

[0022] Another object of the present invention is to provide a concrete made of the modified submarine tunnel slag aggregate, comprising the following components in parts by weight: 270-300 parts of cement, 60-80 parts of fly ash, 40-50 parts of metakaolin, 10-15 parts of sepiolite, 700-780 parts of sand, 1010-1080 parts of modified submarine tunnel slag aggregate, 155-170 parts of water, 4-6 parts of water reducer, 1.0-1.3 parts of polyvinyl pyrrolidone, and 5-8 parts of silica fume.

[0023] On the one hand, the metakaolin in the concrete of the present invention can react with calcium hydroxide to generate additional calcium silicate hydrate (CSH) and calcium aluminate hydrate (CAH), thereby increasing the compactness and strength of the concrete and improving the CSH gel content in the concrete. The CSH gel content is positively correlated with the cement-based solidified free chloride ions, and the fine metakaolin particles are filled in the gaps between the cement matrix to improve the microstructure of the concrete. On the other hand, the highly active Al2O3 in the concrete can directly react with the hydration products CH and Cl- to be converted into Friedel's salt, thereby realizing the solidification of chloride ions and reducing the content of free chloride ions in the cement base.

[0024] Preferably, the sepiolite is a calcined modified sepiolite obtained by calcining original sepiolite at 500-550°C.

[0025] The invention introduces sepiolite into concrete to improve various properties of concrete. First, calcination can change the pore structure of sepiolite and stimulate the Mg 2+ First, the adsorption active sites of sepiolite can be used to improve the adsorption capacity of chloride ions and sulfate ions, which can further reduce the content of chloride ions and sulfate ions flowing out of the modified submarine tunnel slag aggregate and free in the concrete. In addition, the rupture and destruction of Si-O-Si bonds in sepiolite can also form a complex between the silanol group and the adsorbate; second, sepiolite has volcanic ash activity and excellent water absorption and internal curing effect, which can promote the formation of hydration products CSH, improve the interface transition zone, fill the pores of the cement matrix, and improve the mechanical properties and durability of concrete; third, sepiolite has a good fiber structure. Under the microscopic level, it contains bundles of long fibers and blocks of short fibers. When added to submarine tunnel slag aggregate concrete, it can form a three-dimensional fiber network structure, effectively inhibit the expansion of cracks, improve the tensile strength, crack resistance and toughness of concrete, and reduce the formation and development of cracks. At the same time, fine sepiolite fibers can be filled in the pores and microcracks of concrete, reduce the porosity and connectivity of concrete, and effectively prevent the penetration and freeing of chloride ions in the internal aggregate and external harmful substances.

[0026] The polyvinyl pyrrolidone (PVP) in the concrete of the present invention can effectively optimize the rheological properties of the concrete under the cement-fly ash-metakaolin-sepiolite quaternary adhesive system, improve the construction pumpability, prevent the concrete from bleeding and segregation, and strengthen the compactness of the molding. At the same time, by utilizing its bonding properties, a certain network structure can be formed during the concrete hardening process to improve the compactness of the concrete. More importantly, PVP is an organic surfactant with adsorption properties. When introduced into the concrete structure, it can be adsorbed on the surface of the steel bar and form an adsorption protective film, which is very effective for the medium, especially the corrosive Cl - It plays a barrier role, inhibits the occurrence of steel bar corrosion, and promotes the formation of a passivation film on the steel bar surface.

[0027] Preferably, the specific surface area of ​​the metakaolin is 600-700m 2 / kg, Al2O3 content ≥40%.

[0028] Preferably, the average molecular weight of the polyvinyl pyrrolidone is 1,300,000, and the pH value in a 10 wt% aqueous solution is 7.0-9.0.

[0029] Preferably, the silica content in the silica ash is ≥80wt%, and the specific surface area is 25-28m 2 / g.

[0030] Another object of the present invention is to provide a method for preparing the concrete, comprising the following steps:

[0031] P1. Weigh each component by weight;

[0032] P2. The cement, fly ash, metakaolin, sepiolite and silica fume are mixed and stirred evenly, and then the modified submarine tunnel slag aggregate, sand, 2 / 3 of the water reducer and 2 / 3 of the water are added, and stirring is continued until a uniform state is obtained to obtain a slurry;

[0033] P3. Add the polyvinyl pyrrolidone, the remaining 1 / 3 of the water reducer and 1 / 3 of the water, and stir evenly to obtain an undersea tunnel slag aggregate concrete slurry.

[0034] In the steps, 2 / 3 of the water reducer refers to 2 / 3 of the total amount of the water reducer; 2 / 3 of the water refers to 2 / 3 of the total amount of the water.

[0035] The present invention first mixes cement, fly ash, metakaolin, sepiolite and silica fume, which is conducive to uniform dispersion of sepiolite in the slurry and improves the mechanical properties and durability of the test piece after molding.

[0036] Compared with the prior art, the present invention is beneficial in that:

[0037] (1) The modification treatment of submarine tunnel slag aggregate by the present invention includes weakening ion competition, plugging cracks, controlling the release of chloride ions, and solidification adsorption. That is, the submarine tunnel slag aggregate is first placed in a barium hydroxide solution to weaken the competition of sulfate ions for chloride ions in LDHs, and at the same time, the formation of insoluble barium sulfate precipitation combined with sodium silicate can block aggregate microcracks, reduce the channels for chloride ions inside the aggregate to precipitate to the surface, and promote the formation of CSH gel, a hydration product at the interface of the slag aggregate; then, ethyl cellulose is used to form a coating layer to effectively encapsulate the chloride ions in the aggregate and achieve controlled release of chloride ion diffusion rate; finally, an ion exchange chitosan gel solution is used to achieve the effect of nitrate intercalation Mg-Al-LDHs solidification of chloride ions, weakening the influence of nitrate, and strengthening the interface of the chitosan network structure, which can effectively weaken the high content of chloride ions and sulfate ions on the surface and inside of the submarine tunnel slag aggregate to be free to the outside of the aggregate, and at the same time solve the problem of poor concrete mechanics and crack resistance caused by many microcracks on the surface and inside of the submarine tunnel slag aggregate.

[0038] (2) The present invention improves the comprehensive performance of submarine tunnel slag aggregate concrete mainly from the following two aspects: first, by modifying the submarine tunnel slag aggregate, the high content of chloride ions and sulfate ions on the surface and inside of the submarine tunnel slag aggregate are fully weakened and released to the outside of the aggregate, and at the same time, the problem of poor concrete mechanical and crack resistance caused by the many micro cracks on the surface and inside of the submarine tunnel slag aggregate is solved; second, the proportion of submarine tunnel slag aggregate concrete is optimized to increase the CSH gel content of concrete, densely seal pores and enhance crack resistance. Under the joint action of metakaolin, sepiolite and polyvinyl pyrrolidone, the content of free chloride ions in concrete is effectively reduced, and the adverse effects of submarine tunnel slag aggregate on the performance of concrete series compared with ordinary aggregate are further weakened, thereby ensuring the mechanical properties, crack resistance and corrosion resistance of concrete, extending the service life of engineering structures, realizing high-value utilization of solid waste, and achieving the goals of energy conservation and emission reduction, carbon reduction and environmental protection, and green building materials. DETAILED DESCRIPTION

[0039] The technical solution of the present invention will be described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0040] In the following embodiments and comparative examples, the subsea tunnel slag aggregate is derived from rocks obtained during the construction of the subsea tunnel by drilling and blasting excavation or shield excavation, and then crushed to produce crushed stone aggregate with a particle size of 5 to 20 mm.

[0041] The present invention can adopt any nitrate intercalated Mg-Al-LDHs of the prior art. As an example only, the preparation method of nitrate intercalated Mg-Al-LDHs is as follows:

[0042] (1) Calcine magnesium aluminum hydrotalcite at 455°C for 3.5 h and cool to room temperature to obtain calcined Mg-Al-LDHs powder; (2) Mix 1 g of Mg-Al-LDHs powder with 200 ml of 0.2 mol / L NaNO3 salt solution and stir at low speed for 12 h in a closed container at room temperature to achieve ion exchange equilibrium; (3) Filter, wash twice with deionized water, and dry at 80±5°C for 8 h to obtain nitrate intercalated Mg-Al-LDHs.

[0043] In the following examples and comparative examples, unless otherwise specified, cement is ordinary Portland cement P·O 52.5; the specific surface area of ​​metakaolin is 600-700m 2 / kg, Al2O3 content ≥40%; silica content in silica ash ≥80wt%, specific surface area 25~28m 2 / g; the sepiolite is a calcined modified sepiolite obtained by ultrasonically treating original sepiolite in deionized water, drying it, and then calcining it at 500-550°C for 2-3h; the average molecular weight of polyvinyl pyrrolidone is 1300000, and the pH value in a 10wt% aqueous solution is 7.0-9.0; the water reducer is a polycarboxylic acid high-performance water reducer with a water reduction rate of 28%; the fly ash can be F-class II fly ash with a fineness of 20-25μm and a water requirement ratio of 95-105%; the sand is II-class coarse sand with a fineness modulus of 3.3-3.7 and a mud content of no more than 4%.

[0044] Example 1

[0045] This embodiment provides a method for preparing modified submarine tunnel slag aggregate, comprising the following steps:

[0046] S1. The subsea tunnel slag aggregate was washed with water, dried, and immersed in a 0.5 mol / L barium hydroxide solution for 10 h, and then immersed in a 6 wt% sodium silicate solution for 2 h, and then naturally dried;

[0047] S2. The submarine tunnel slag aggregate obtained in step S1 is placed in an ethyl cellulose solution (a mixed solvent of ethanol and ethyl acetate in a volume ratio of 7:3, and the mass fraction of ethyl cellulose is 12%) and soaked for 60 minutes. After being taken out and dried, it is placed in an ion exchange chitosan gel solution and soaked for 3 hours. After being taken out and naturally dried, the modified submarine tunnel slag aggregate is obtained.

[0048] Diethyl phthalate is also added to the ethyl cellulose solution, and the added amount is 12% of the weight of the ethyl cellulose.

[0049] The ion exchange chitosan gel solution is prepared by mixing nitrate intercalated Mg-Al-LDHs and chitosan hydrogel in a mass ratio of 1:4; the chitosan hydrogel is prepared by stirring and mixing chitosan and 2wt% acetic acid aqueous solution, wherein the mass concentration of chitosan is 6%.

[0050] Example 2

[0051] This embodiment provides a method for preparing modified submarine tunnel slag aggregate, comprising the following steps:

[0052] S1. The subsea tunnel slag aggregate was washed with water, dried, and immersed in a 1.0 mol / L barium hydroxide solution for 8 h, then taken out and immersed in a 10 wt% sodium silicate solution for 1.5 h, and then naturally dried;

[0053] S2. The submarine tunnel slag aggregate obtained in step S1 is placed in an ethyl cellulose solution (with a mass fraction of 18%) and soaked for 40 minutes. After being taken out and dried, it is placed in an ion exchange chitosan gel solution and soaked for 4 hours. After being taken out and naturally dried, the modified submarine tunnel slag aggregate is obtained.

[0054] Diethyl phthalate is also added to the ethyl cellulose solution, and the added amount is 8% by weight of the ethyl cellulose.

[0055] The ion exchange chitosan gel solution is prepared by mixing nitrate intercalated Mg-Al-LDHs and chitosan hydrogel in a mass ratio of 1:2.5; the chitosan hydrogel is prepared by stirring and mixing chitosan and 2wt% acetic acid aqueous solution, wherein the mass concentration of chitosan is 3%.

[0056] Example 3

[0057] This embodiment provides a method for preparing modified submarine tunnel slag aggregate, comprising the following steps:

[0058] S1. The subsea tunnel slag aggregate was washed with water, dried, and immersed in a 0.6 mol / L barium hydroxide solution for 9 h, then taken out and immersed in a 7 wt% sodium silicate solution for 100 min, and then naturally dried;

[0059] S2. The submarine tunnel slag aggregate obtained in step S1 is placed in an ethyl cellulose solution (with a mass fraction of 13%) and soaked for 50 minutes. After being taken out and dried, it is placed in an ion exchange chitosan gel solution and soaked for 3.5 hours. After being taken out and naturally dried, the modified submarine tunnel slag aggregate is obtained.

[0060] Diethyl phthalate is also added to the ethyl cellulose solution, and the added amount is 10% by weight of the ethyl cellulose.

[0061] The ion exchange chitosan gel solution is prepared by mixing nitrate intercalated Mg-Al-LDHs and chitosan hydrogel in a mass ratio of 1:2.7; the chitosan hydrogel is prepared by stirring and mixing chitosan and 1.5wt% acetic acid aqueous solution, wherein the mass concentration of chitosan is 4%.

[0062] Comparative Example 1

[0063] The preparation method of the modified submarine tunnel slag aggregate in this comparative example has the following steps: the submarine tunnel slag aggregate is washed and dried with water, and then immersed in a 0.6 mol / L barium hydroxide solution for 9 hours, taken out and immersed in a 7 wt % sodium silicate solution for 100 minutes, and then naturally dried to obtain the modified submarine tunnel slag aggregate.

[0064] That is, compared with Example 3, step S2 is omitted in this comparative example.

[0065] Comparative Example 2

[0066] The preparation method of the modified submarine tunnel slag aggregate in this comparative example has the following steps: soaking the submarine tunnel slag aggregate in an ethyl cellulose solution (with an ethyl cellulose mass fraction of 13%) for 50 minutes, taking it out and drying it, then soaking it in an ion exchange chitosan gel solution for 3.5 hours, taking it out and drying it naturally to obtain the modified submarine tunnel slag aggregate.

[0067] That is, compared with Example 3, step S1 is omitted in this comparative example.

[0068] Comparative Example 3

[0069] The steps of the preparation method of the modified submarine tunnel slag aggregate of this comparative example are as follows:

[0070] S1. Soak the subsea tunnel slag aggregate in an ethyl cellulose solution (with a mass fraction of 13%) for 50 minutes, take it out and dry it, then soak it in an ion exchange chitosan gel solution for 3.5 hours, and take it out and dry it naturally;

[0071] S2. The submarine tunnel slag aggregate obtained in step S1 is placed in a 0.6 mol / L barium hydroxide solution and soaked for 9 hours. After being taken out, it is placed in a 7 wt % sodium silicate solution and soaked for 100 minutes. After being taken out, it is naturally dried to obtain modified submarine tunnel slag aggregate.

[0072] That is, compared with Example 3, the order of steps S1 and S2 is swapped in this comparative example.

[0073] Comparative Example 4

[0074] The steps of the preparation method of the modified submarine tunnel slag aggregate of this comparative example are as follows:

[0075] S1. The subsea tunnel slag aggregate was washed with water, dried, and immersed in a 0.6 mol / L barium hydroxide solution for 9 h, then taken out and immersed in a 7 wt% sodium silicate solution for 100 min, and then naturally dried;

[0076] S2. The submarine tunnel slag aggregate obtained in step S1 is placed in an ethyl cellulose solution (with a mass fraction of 13%) and soaked for 50 minutes. After being taken out and dried, it is placed in an ion exchange solution and soaked for 3.5 hours. After being taken out and naturally dried, the modified submarine tunnel slag aggregate is obtained.

[0077] Diethyl phthalate is also added to the ethyl cellulose solution, and the added amount is 10% by weight of the ethyl cellulose.

[0078] The ion exchange solution was prepared by mixing nitrate-intercalated Mg-Al-LDHs and water in a mass ratio of 1:2.7.

[0079] That is, compared with Example 3, this comparative example lacks chitosan hydrogel.

[0080] The modified submarine tunnel slag aggregates of Examples 1 to 3 and Comparative Examples 1 to 4 were tested for relevant properties, and the unmodified submarine tunnel slag aggregates were used as the control group; the crushing value of the modified submarine tunnel slag aggregates was tested with reference to the standard GB / T 14685-2022 "Pebbles and Crushed Stones for Construction". The smaller the crushing value, the higher the strength of the aggregate. With reference to the standard GB / T14684-2022 "Sand for Construction", the chloride content of the aggregate was detected by titration; from each example, 5 relatively large-sized aggregates were randomly selected, and the number and depth of cracks on the surface of the aggregates were observed using a 50x electronic magnifying glass to judge the crack situation. The number of cracks was divided into four levels: few, medium, more, and more, and the overall coarseness of the cracks was divided into four levels: fine, fine, coarse, and coarse. The test results are shown in Table 1.

[0081] Table 1 Test results of subsea tunnel slag aggregate properties

[0082]

[0083] From the test results in Table 1, it can be seen that the crushing value of the unmodified submarine tunnel slag aggregate is 16.8%, the apparent cracks of the aggregate are large in number and coarse, and the chloride ion content is as high as 0.12%, which does not meet the standard of concrete aggregate. The modified submarine tunnel slag aggregate obtained by the preparation method of the present invention has an aggregate crushing value of about 10.2-10.4% overall, which is more than 38% lower than the unmodified aggregate, and the aggregate crushing resistance is significantly improved, and the number and width of the surface cracks of the aggregate are greatly reduced, which is due to the fact that the insoluble precipitation of barium sulfate combined with sodium silicate can block the micro cracks of the aggregate. While filling the cracks, sodium silicate plays a bonding and strengthening role on the insoluble precipitation of barium sulfate and the aggregate, thereby improving the compressive strength of the aggregate. The chloride ion content of the modified submarine tunnel slag aggregate in Examples 1 to 3 is all 0.02%, which is 83% lower than the unmodified aggregate. This shows that the chloride ions on the surface and inside of the submarine tunnel slag aggregate are effectively solidified and adsorbed by the modification, and the free chloride ions precipitated into the solution by the aggregate are greatly reduced.

[0084] Compared with Example 3, Comparative Example 1 was only processed by step S1. Compared with the unmodified aggregate, it has a significant improvement effect in aggregate crushing value and surface crack condition, but the improvement effect on chloride ion content index is poor. The chloride ion content test result is 0.08%. Water washing and barium hydroxide solution immersion can reduce the chloride content on the surface of submarine tunnel slag aggregate to a certain extent, but the reduction is small, and with the extension of time, the chloride ions inside the aggregate will precipitate to the surface; Compared with Example 3, Comparative Example 2 was only processed by step S2, and its aggregate crushing value and surface crack condition The improvement effect is poor, and the chloride ion content is 0.05%, which is about 42% of the unmodified aggregate. This shows that the coating layer formed by ethyl cellulose and the ion exchange chitosan gel solution can play a good role in reducing the free and adsorption solidification of chloride ions. However, since the modified aggregate has not been treated to weaken the competition of sulfate ions and block microcracks, more cracks will form together with channels to make the chloride ions inside the aggregate free to the surface in large quantities. At the same time, the sulfate ions contained in the aggregate will compete with the chloride ions, which will affect the effect of nitrate intercalation Mg-Al-LDHs solidifying chloride ions to a certain extent. Compared with Example 3, Comparative Example 3 swaps the order of steps S1 and S2. In terms of the test data results, the crushing value, chloride ion content, and aggregate apparent cracks of Comparative Example 3 are slightly improved compared with Comparative Example 2, but the improvement effect is not obvious, and there is still a certain gap compared with Example 3. Compared with Example 3, Comparative Example 4 lacks chitosan hydrogel, and the compression value of Comparative Example 4 is basically close to that of Comparative Example 1. However, due to the partial operation of S2 in Comparative Example 4, the presence of the encapsulating layer of ethyl cellulose and diethyl phthalate makes the chloride ion content of Comparative Example 4 less than that of Comparative Example 1, but still higher than that of Comparative Example 2. This shows that due to the lack of chitosan hydrogel in Comparative Example 4, the nitrate intercalated Mg-Al-LDHs basically cannot play the effect of curing chloride ions.

[0085] Comparative Examples 1 to 4 illustrate that the modification steps of the present invention are indispensable, and the modification order is also crucial to the modification effect. Changes in conditions will result in the inability to weaken the impact of the dual defects of high chloride ion content and many cracks in the submarine tunnel slag aggregate on the performance of concrete.

[0086] Example 4

[0087] This embodiment provides concrete, including the following components in parts by weight: 270 parts of cement, 70 parts of fly ash, 50 parts of metakaolin, 15 parts of sepiolite, 760 parts of sand, 1030 parts of modified submarine tunnel slag aggregate of Example 1, 160 parts of water, 6 parts of water reducing agent, 1.1 parts of polyvinyl pyrrolidone, and 8 parts of silica fume;

[0088] The method for preparing lightweight aggregate concrete of this embodiment comprises the following steps:

[0089] S1. Weigh each component by weight;

[0090] S2. The cement, fly ash, metakaolin, sepiolite, and silica fume were mixed and stirred for 20 to 30 seconds, and then the modified submarine tunnel slag aggregate, sand, 2 / 3 of the water reducer and 2 / 3 of the water of Example 1 were added, and the mixture was stirred for 40 to 50 seconds until a uniform state was obtained to obtain a slurry;

[0091] S3. Then add polyvinyl pyrrolidone, the remaining 1 / 3 of the water reducer and 1 / 3 of the water, and stir for 60s to 90s to obtain a submarine tunnel slag aggregate concrete slurry.

[0092] Example 5

[0093] This embodiment provides concrete, including the following components in parts by weight: 280 parts of cement, 70 parts of fly ash, 45 parts of kaolin, 12 parts of sepiolite, 740 parts of sand, 1050 parts of modified submarine tunnel slag aggregate of Example 3, 165 parts of water, 5 parts of water reducer, 1.2 parts of polyvinyl pyrrolidone, and 7 parts of silica fume; the preparation method of the concrete is the same as that of Example 4.

[0094] Example 6

[0095] This embodiment provides concrete, including the following components in parts by weight: 280 parts of cement, 80 parts of fly ash, 48 parts of kaolin, 14 parts of sepiolite, 750 parts of sand, 1040 parts of modified submarine tunnel slag aggregate of Example 3, 155 parts of water, 4 parts of water reducer, 1.2 parts of polyvinyl pyrrolidone, and 5 parts of silica fume; the preparation method of the concrete is the same as that of Example 4.

[0096] Example 7

[0097] This embodiment provides concrete, comprising the following components in parts by weight: 290 parts of cement, 65 parts of fly ash, 42 parts of metakaolin, 10 parts of sepiolite, 730 parts of sand, 1060 parts of modified submarine tunnel slag aggregate of embodiment 2, 165 parts of water, 6 parts of water reducing agent, 10 parts of polyvinyl pyrrolidone, and 7 parts of silica fume; the preparation method of the concrete is the same as that of embodiment 4.

[0098] Example 8

[0099] This embodiment provides concrete, including the following components in parts by weight: 300 parts of cement, 60 parts of fly ash, 40 parts of kaolin, 11 parts of sepiolite, 720 parts of sand, 1070 parts of modified submarine tunnel slag aggregate of Example 3, 170 parts of water, 6 parts of water reducer, 1.3 parts of polyvinyl pyrrolidone, and 6 parts of silica fume; the preparation method of the concrete is the same as that of Example 4.

[0100] Comparative Example 5

[0101] The difference between Comparative Example 5 and Example 4 is that unmodified submarine tunnel slag aggregate is used instead of the modified submarine tunnel slag aggregate of Example 1.

[0102] Comparative Example 6

[0103] The difference between Comparative Example 6 and Example 4 is that the modified submarine tunnel slag aggregate of Comparative Example 1 is used instead of the modified submarine tunnel slag aggregate of Example 1.

[0104] Comparative Example 7

[0105] The difference between Comparative Example 7 and Example 4 is that the modified submarine tunnel slag aggregate of Comparative Example 2 is used instead of the modified submarine tunnel slag aggregate of Example 1.

[0106] Comparative Example 8

[0107] The difference between Comparative Example 8 and Example 4 is that the modified submarine tunnel slag aggregate of Comparative Example 3 is used instead of the modified submarine tunnel slag aggregate of Example 1.

[0108] Comparative Example 9

[0109] The difference between Comparative Example 9 and Example 4 is that the modified submarine tunnel slag aggregate of Comparative Example 4 is used instead of the modified submarine tunnel slag aggregate of Example 1.

[0110] Comparative Example 10

[0111] The difference between Comparative Example 10 and Example 4 is that the sepiolite is replaced by fly ash.

[0112] The mechanical properties, crack resistance, impermeability and chloride ion penetration resistance of the concrete of Examples 4 to 8 and Comparative Examples 5 to 10 were tested. The compressive strength of the concrete was tested with reference to GB / T 50081-2002 "Standard for Test Methods of Mechanical Properties of Ordinary Concrete"; the crack resistance and impermeability of the concrete were tested with reference to GB / T 50082-2009 "Standard for Test Methods of Long-term Performance and Durability of Ordinary Concrete", and the "Anti-crack Plate Test" was used to determine the crack resistance of the concrete. The test results were expressed as the total crack area per unit area calculated. The smaller the value, the better the crack resistance. The anti-chloride ion penetration performance of the concrete was tested by the electric flux method to characterize the concrete's ability to resist chloride ion migration; the water-soluble chloride ion content in the ready-mixed concrete and hardened concrete was tested with reference to JG / T 322-2013 "Technical Specifications for Detection of Chloride Ion Content in Concrete". The test results are shown in Table 2.

[0113] Table 2 Concrete performance test results

[0114]

[0115]

[0116] From the test results in Table 2, it can be seen that the 28d compressive strength of Examples 4 to 8 is generally around 47-52 MPa, which increases slightly with the increase of cement dosage, the electric flux is generally lower than 370C, and the total cracking area per unit area is 100mm 2 / m 2 Within 0.1%, cracks are almost invisible to the naked eye, and the crack resistance level is V. In terms of chloride ion content of concrete, the chloride ion content of premixed concrete is around 0.11-0.13%, and the water-soluble chloride ion content of hardened concrete is still lower than the control standard of 0.3%, which shows that the modified submarine tunnel slag aggregate prepared by the present invention has good mechanical properties, density, crack resistance and corrosion resistance, which can effectively extend the service life of engineering structures, realize high-value utilization of solid waste, and achieve the goals of energy conservation and emission reduction, carbon reduction, environmental protection, and green building materials.

[0117] Compared with Example 4, Comparative Example 5 is a concrete prepared using unmodified submarine tunnel slag aggregate, and its 28d compressive strength is reduced by 5.8MPa, and the total cracking area per unit area is 229mm 2 / m 2, the crack resistance is level IV, and the water-soluble chloride ion content of premixed and hardened concrete exceeds 0.3% and reaches 0.5%; the test results of comparative examples 6 and 7 prove that the insoluble precipitation of barium sulfate combined with sodium silicate can block micro-cracks in aggregates, promote the formation of CSH gel, a hydration product at the interface of tunnel slag aggregates, and improve the strength of concrete. The interface enhancement effect of chitosan network structure can also improve the strength and crack resistance of the interface of submarine tunnel slag aggregates to a certain extent. The coating layer of ethyl cellulose and diethyl phthalate effectively wraps the chloride ions in the aggregates and realizes the controlled release of chloride ion diffusion rate. The ion exchange chitosan gel solution realizes the nitrate intercalation Mg-Al-LDHs solidification of chloride ions and weakens the influence of nitrate ions, reducing the high content of chloride ions and sulfate ions on the surface and inside of submarine tunnel slag aggregates to the outside of the aggregates. Comparative Example 8 uses the modified submarine tunnel slag aggregate of Comparative Example 3, and its 28d compressive strength and total cracking area per unit area are slightly better than those of Comparative Example 7. Because the modification treatment method of the submarine tunnel slag aggregate in Comparative Example 8 is to exchange the order of S1 and S2 in the modification steps of the present invention, the effect of S1 is limited, so the test results of the water-soluble chloride ion content of the ready-mixed concrete and the water-soluble chloride ion content of the hardened concrete in Comparative Example 8 are better than those in Comparative Example 7, but there is still a certain gap compared with Examples 4-8; the test results of Comparative Example 9 prove that the chitosan hydrogel in the slag aggregate has a good improvement effect on the cement-based interface, and can better improve the effect of nitrate intercalation Mg-Al-LDHs. The test results of Comparative Example 10 demonstrate that sepiolite has a good effect on improving the mechanical properties, crack resistance and chloride ion adsorption capacity of concrete.

[0118] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A method for preparing modified submarine tunnel slag aggregate, characterized in that: The following steps are involved: S1. Soak the submarine tunnel slag aggregate in a barium hydroxide solution, take it out and soak it in a sodium silicate solution, take it out and dry it; S2. The tunnel slag aggregate obtained in step S1 is soaked in an ethyl cellulose solution, taken out and dried, and then soaked in an ion exchange chitosan gel solution, taken out and dried to obtain the modified submarine tunnel slag aggregate; The ion exchange chitosan gel solution comprises nitrate intercalated Mg-Al-LDHs and chitosan hydrogel.

2. The method for preparing a modified submarine tunnel slag aggregate according to claim 1, characterized in that: The concentration of the barium hydroxide solution is 0.5-1.0 mol / L, the concentration of the sodium silicate solution is 6wt%-10wt%, and the concentration of the ethyl cellulose in the ethyl cellulose solution is 12wt%-18wt%.

3. The method for preparing a modified submarine tunnel slag aggregate according to claim 1, characterized in that: The mass ratio of the nitrate intercalated Mg-Al-LDHs to the chitosan hydrogel is 1:(2.5-4).

4. The method for preparing a modified submarine tunnel slag aggregate according to claim 1, characterized in that: The chitosan hydrogel is prepared by mixing chitosan with acetic acid solution, and the concentration of the chitosan is 3wt% to 6wt%.

5. The method for preparing a modified submarine tunnel slag aggregate according to claim 1, characterized in that: The ethyl cellulose solution also includes diethyl phthalate, and the mass of the diethyl phthalate is 8% to 12% of the ethyl cellulose.

6. The method for preparing modified submarine tunnel slag aggregate according to claim 1, characterized in that: The subsea tunnel slag aggregate is immersed in the barium hydroxide solution for 8 to 10 hours, immersed in the sodium silicate solution for 1.5 to 2 hours, immersed in the ethyl cellulose solution for 40 to 60 minutes, and immersed in the ion exchange chitosan gel solution for 3 to 4 hours.

7. Modified submarine tunnel slag aggregate prepared by the preparation method according to any one of claims 1 to 6.

8. A concrete made from the modified submarine tunnel slag aggregate as claimed in claim 7, characterized in that: The invention comprises the following components in parts by weight: 270-300 parts of cement, 60-80 parts of fly ash, 40-50 parts of metakaolin, 10-15 parts of sepiolite, 700-780 parts of sand, 1010-1080 parts of modified submarine tunnel slag aggregate, 155-170 parts of water, 4-6 parts of water reducing agent, 1.0-1.3 parts of polyvinyl pyrrolidone and 5-8 parts of silica fume.

9. The concrete according to claim 8, characterized in that The sepiolite is a calcined modified sepiolite obtained by calcining original sepiolite at 500-550°C.

10. The method for preparing concrete according to claim 8 or 9, characterized in that: The following steps are involved: P1. Weigh each component by weight; P2. The cement, fly ash, metakaolin, sepiolite and silica fume are mixed and stirred evenly, and then the modified submarine tunnel slag aggregate, sand, 2 / 3 of the water reducer and 2 / 3 of the water are added, and stirring is continued until a uniform state is obtained to obtain a slurry; P3. Add the polyvinyl pyrrolidone, the remaining 1 / 3 of the water reducer and 1 / 3 of the water, and stir evenly to obtain an undersea tunnel slag aggregate concrete slurry.

Citation Information

Patent Citations

  • Microbial sea sand concrete building material product

    CN110963774A

  • Polymer-based sea sand concrete and preparation method thereof

    CN113387613A

  • Preparation method of pre-wrapped toughened coral aggregate and seawater and sea sand coral aggregate concrete

    CN115353313A

  • Concrete for heating and shaping whole tunnel hole slag aggregate and preparation method thereof

    CN115536341A

Cited By

  • Salt-containing seabed tunnel hole slag fluidized solidified soil and preparation method and application thereof

    CN122608350A